2005
DOI: 10.3200/psfl.50.1.29-34
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Teacher Efficacy for Working With Culturally Diverse Students

Abstract: Teachers exert a potent influence over the achievement of all students, lowincome culturally diverse students in particular. Although recent research has confirmed that teacher involvement is critical for promoting academic engagement of low-income and ethnically diverse students, other literature suggests that teachers have lower expectations for and fewer interactions with these children. These findings have prompted calls for promoting teacher self-efficacy for working with children from diverse backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 17 publications
2
59
2
3
Order By: Relevance
“…In addition, participation in special education training improve teachers' sense of selfefficacy [45,61].…”
Section: Teachers' Self-efficacy Beliefsmentioning
confidence: 99%
“…In addition, participation in special education training improve teachers' sense of selfefficacy [45,61].…”
Section: Teachers' Self-efficacy Beliefsmentioning
confidence: 99%
“…Bandura (1997) has suggested that efficacy cognitions not only influence how people behave but they also elicit thought patterns and affective reactions to tasks that challenge personal capabilities (see also Pajares & Schunk, 2005;Skaalvik & Bong, 2005). Teachers with high self-efficacy are able to attain personal accomplishments and well-being, reduce stress, and are less vulnerable to depression, experience less negative emotions in teaching, and are more effective in meeting the needs of culturally diverse student groups (Ashton, Olejnik, & Croker, 1982;Bandura, 1994;Greenwood, Olejnik, & Parkay, 1990;Tucker, Porter, Reinke, Herman, Ivery, Mack, & Jackson, 2005). Conversely, people with low self efficacy are face difficulties in commitments to the goals they choose to pursue, blame themselves for their failure, believe that things are tougher than they really are, a belief that fosters anxiety and stress as they engage in a task, are slow to recover after failures or setbacks, and easily fall victim to depression (Bandura, 1994;Fiori, Mcilvane, Brown, & Antonucci, 2006;Muris, 2001;Pajares & Schunk, 2005;Ross, 1998;Stephanou, 2004;Wheatley, 2005).…”
Section: Emotionsmentioning
confidence: 99%
“…Soon, children were saying things like, ''that boy in the yellow hat,'' or that girl on the jungle gym'' rather than ''that white boy'' or ''that black girl.'' Teachers have a powerful influence on the achievement of students that are culturally diverse and/or low income and collaborative teacher involvement with one another has been found to have a crucial impact on that effect being a positive one Tucker et al (2005). When teachers fail to work together to create culturally responsive classrooms, the pressures upon teachers to respond to this need traces to the high attrition of teachers in urban schools McKinney et al (2005).…”
Section: Faculty Bondingmentioning
confidence: 98%